Molecular Basis for Two Stereoselective Diels–Alderases that Produce Decalin Skeletons. (5th July 2021) - Fujiyama, Keisuke; Kato, Naoki; Re, Suyong; Kinugasa, Kiyomi; Watanabe, Kohei; Takita, Ryo; Nogawa, Toshihiko; Hino, Tomoya; Osada, Hiroyuki; Sugita, Yuji; Takahashi, Shunji; Nagano, Shingo
Abstract: Enzymes catalyzing [4+2] cycloaddition have attracted increasing attention because of their key roles in natural product biosynthesis. Here, we solved the X‐ray crystal structures of a pair of decalin synthases, Fsa2 and Phm7, that catalyze intramolecular [4+2] cycloadditions to form enantiomeric decalin scaffolds during biosynthesis of the HIV‐1 integrase inhibitor equisetin and its stereochemical opposite, phomasetin. Computational modeling, using molecular dynamics simulations as well as quantum chemical calculations, demonstrates that the reactions proceed through synergetic conformational constraints assuring transition state‐like substrates folds and their stabilization by specific protein‐substrate interactions. Site‐directed mutagenesis experiments verified the binding models. Intriguingly, the flexibility of bound substrates is largely different in two enzymes, suggesting the distinctive mechanism of dynamics regulation behind these stereoselective reactions. The proposed reaction mechanism herein deepens the basic understanding how these enzymes work but also provides a guiding principle to create artificial enzymes. Abstract : Powerful combination of experimental methods and calculations highlights the distinct molecular mechanisms underlying stereoselective [4+2] cycloadditions catalyzed by a pair of decalin synthases, Fsa2 and Phm7, that catalyze intramolecular cycloadditions to form enantiomeric decalin scaffolds. Our proposed mechanism would open a new window on the enzymatic [4+2] cycloadditions.